Diagnosis of whooping cough in Switzerland: differentiating Bordetella pertussis from Bordetella holmesii by polymerase chain reaction. - Laure F Pittet; Stéphane Emonet; Patrice François; Eve-Julie Bonetti; Jacques Schrenzel; Melanie Hug; Martin Altwegg; Claire-Anne Siegrist; Klara M Posfay-Barbe (PLoS ONE)
Bordetella holmesii, an emerging pathogen, can be misidentified as Bordetella pertussis by routine polymerase chain reaction (PCR). In some reports, up to 29% of the patients diagnosed with pertussis have in fact B. holmesii infection and invasive, non-respiratory B. holmesii infections have been reported worldwide. This misdiagnosis undermines the knowledge of pertussis' epidemiology, and may lead to misconceptions on pertussis vaccine's efficacy. Recently, the number of whooping cough cases has increased significantly in several countries. The aim of this retrospective study was to determine whether B. holmesii was contributing to the increase in laboratory-confirmed cases of B. pertussis in Switzerland. A multiplex species-specific quantitative PCR assay was performed on 196 nasopharyngeal samples from Swiss patients with PCR-confirmed Bordetella infection (median age: 6 years-old, minimum 21 days-old, maximum 86 years-old), formerly diagnosed as Bordetella pertussis (IS481+). No B. holmesii (IS481+, IS1001-, hIS1001+) was identified. We discuss whether laboratories should implement specific PCR to recognize different Bordetella species. We conclude that in Switzerland B. holmesii seems to be circulating less than in neighboring countries and that specific diagnostic procedures are not necessary routinely. However, as the epidemiological situation may change rapidly, periodic reevaluation is suggested.